MARKETING MIX ON PURCHASE DECISION OF HYDROPONIC VEGETABLES - Edi Usman (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2023)
The need for vegetables is increasing in line with public awareness about health. During the Covid-19 virus pandemic, the demand for hydroponic vegetables continued to increase. Media hydroponics is farming without a soil culture, so that vegetables emerge from hydroponic farming systems that are more hygienic and healthy because they don't use pesticides. This study aims to quantitatively analyze the relationship or influence between the independent variables product (XI), price (X2), promotion (X3), place (X4) on the dependent variable on the decision to purchase hydroponic vegetables (Y). The data used in this study are primary and secondary data. The results showed that the product variable (X1), the purchase decision is positive in other words, the increasing quality of products offered to consumers will increase sales and consumer confidence in the products offered, the price variable (X2) in this analysis is negative with In other words, the increase in the price of the product offered will also reduce the purchasing decision or product demand from consumers, the place variable (X3) on the purchase decision is positive, in other words, the more strategic the location of the business or access to places to sell products offered to consumers, the more increase sales, and the promotion variable (X4) on the purchase decision is positive, in other words, the more active and intense the promotion of the products offered to consumers, the more sales will increase. This promotion can be done in many different ways. advertising on social media as well as tv, radio and newspapers.